Ewolucja badań nad zrównoważeniem finansów publicznych - Janikowski, Łukasz (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2018)
From the 1980s onwards, in developed countries (and not only) we observe an upward trend in the ratio of public debt to GDP. In many countries public debt has exceeded GDP, and in the world’s most indebted country – Japan – has exceeded 250% of GDP and continues to grow rapidly. These figures raise concerns among economists and emerge questions about whether public finances in these countries are on a sustainable path. In order to answer these questions, the criteria for assessing the sustainability of public finances need to be specified. This problem was already investigated by classical economists, but the definition and the formal conditions for a balanced fiscal policy have been specified by economists almost two centuries later. The aim of this article is to present the evolution of theoretical research on the problem of sustainability of public finances